Přímá marketingová komunikace vybrané společnosti - Walter, Viliam (Vysoké učení technické v Brně. Fakulta podnikatelská, 2024)
Diplomová práce se zaměřuje na analýzu přímých marketingových aktivit společnosti Sonepar. Primárně se zabývá prací obchodních zástupců a skutečností, jak je využit čas ve vztahu k prodejním aktivitám. Obsahuje návrh změn k přístupu vedení současných pracovníků a přístupu k procesu školení nových pracovníků, které přispějí ke zvýšení efektivity prodejního týmu společnosti Sonepar.

The diploma thesis focuses on the analysis of direct marketing activities of the Sonepar company. It primarily deals with the work of sales representatives and the facts of how time is used in relation to sales activities. It contains a proposal for changes to the management approach of current employees and the approach to the process of training new employees, which will contribute to increasing the effectiveness of Sonepar's sales team.
Direct Marketing Communication of the Selected Company
Keywords: B2B trhy; přímý marketing; obchodní zástupce; měření výkonu; racionalizace; B2B markets; direct marketing; sales representatives; performance measurement; rationalization